Risk of High Systolic Blood Pressure among the Air Crew in Bangladesh Air Force (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Military flight circumstances have been shown to affect Blood Pressure levels. Hypertension is the most severe threat that relates to myocardial infarction, stroke and kidney failure. Exposure to regular flight environment has been shown to Individuals Blood Pressure levels.Objective: To find out the factors associate to presentation of hypertension in air crew in Bangladesh Air force.Materials and Methods: It was a cross-sectional observational study was conducted among 100 Air Force’ pilots of Bangladesh. Data were sort out from medical record files. Participants filled in a survey about demographics, lifestyle factors and dietary habits. Arterial Blood Pressure (BP) was also measured. Multivariate linear regression was implemented.Results: Two patients had history of hypertension among them 2(100.0%) in high systolic blood pressure. Which was statistically significant (p80 beats per minute) 3.5 (95% CI 0.2% to 52.8%) times the risk for systolic blood pressure. In multivariate analysis, age, history of hypertension and pulse were not statistically significant.Conclusion: BP value of most of the air crew in Bangladesh Air Force’ were within normal range. Few of BP standards have been reported in the study history of hypertension they have moreover family history of HTN. Contrastingly, there were some overweight and fast food eating while few reported not exercising.JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 35-38